Analisis Emas sebagai Instrumen Investasi yang Halal dan Stabil - Salwa Nabihah; Harmon Amir (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze gold as a halal and stable investment instrument from the perspective of Islamic economics. Gold possesses unique characteristics as a real asset that is able to preserve wealth, particularly during periods of global economic uncertainty. However, as gold is classified as a ribawi commodity, its investment transactions must comply with Islamic legal principles, including the prohibition of riba, the obligation of taqabudh, and the clarity of ownership. This research employs a qualitative method using a library research approach by analyzing academic journals, books, DSN–MUI fatwas, and other relevant literature. The findings indicate that gold investment is considered halal provided that it is free from riba fadhl and riba nasi’ah, involves taqabudh either physically or constructively, ensures real ownership of gold, and applies transparent contracts without elements of gharar and maysir. Furthermore, the analysis of gold prices in Indonesia during the 2021–2025 period shows a long-term upward trend with relatively controlled fluctuations, reinforcing gold’s role as a safe haven, hedging asset, and store of value. The integration of price stability with the principles of Islamic jurisprudence demonstrates that gold represents a safe, stable, and sharia-compliant investment instrument that aligns with the objectives of maqāṣid al-sharī‘ah, particularly in safeguarding wealth (hifz al-māl). Therefore, gold can be considered an ideal investment option for Indonesian Muslims when managed in substantive compliance with sharia principles.